NEW TETRANUCLEAR AND MONONUCLEAR OXALATO ORGANOTIN (IV) COMPLEXES WITH MONOCYCLOHEXYLAMMONIUM AS ADVERSE CATION: SYNTHESIS AND INFRARED STUDY - MODOU SARR; AMINATA DIASSE-SARR; LIBASSE DIOP (Journal of Engineering Studies and Research)
Eight new adducts and derivatives have been synthesized and studied by infrared. Discrete, layered or infinite chain structures are suggested with an oxalate behaving as a monodentate, bidentate, monochelating or bichelating ligand, the environment around the tin centres being tetrahedral, cis trigonal bipyramidal or octahedral. In all the studied compounds, supramolecular architectures may be obtained when intermolecular hydrogen bonds are considered.